2000
DOI: 10.1111/j.1745-4522.2000.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Dromedary Milk Fat: Biochemical, Microscopic and Rheological Characteristics

Abstract: Structural and physicochemical characteristics of dromedary milk fat were investigated and compared with those of cow's milk fat. The fatty acid composition of dromedary milk fat showed the presence of very small amounts of short‐chain fatty acids (C4–C12) and a higher content of 16:1 and 18:0. The microscopic study showed a discontinuous phase of globules with a smaller size but presenting a relatively thicker membrane layer. The rheological and the melting studies showed that dromedary milk fat on the one ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 14 publications
5
46
0
1
Order By: Relevance
“…Stearic acid (C18:0) is present at a higher amount in camel milk fat [1,3]. The comparison of the amount of palmitic acid (C16:0) in camel and bovine milk fat is further discussed by the authors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stearic acid (C18:0) is present at a higher amount in camel milk fat [1,3]. The comparison of the amount of palmitic acid (C16:0) in camel and bovine milk fat is further discussed by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…However, Attia et al [3] found that the proportion of C16:0 was lower in dromedary milk fat and Farah et al [6] found that this FA was present in higher quantities in camel milk originating from Kenya.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although data on the general composition of camel's milk is reported by several sources [3,11,12,26], data on the chemical and physical properties of anhydrous Dromedary milk fat polymorphism 435 dromedary milk fat (ADMF), which is the fat isolated from butter, are still scarce. ADMF is an essential nutriment in desert areas with a complex fatty acid composition [2,5,8], which has already been discussed in the first article of this series [9]. As observed for other fats and in the previous study [9], the coupling of X-ray diffraction (XRD) as a function of temperature (XRDT) and differential scanning calorimetry (DSC) is the best technique to characterize the structural and thermal behavior of ADMF [14][15][16][17][18][19][20][21]25].…”
Section: Introductionmentioning
confidence: 99%